2020
DOI: 10.1097/hs9.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cytokine Profiling Identifies GRO‐α and EGF as Potential Biomarkers of Disease Progression in Essential Thrombocythemia

Abstract: Myeloproliferative neoplasms (MPNs) are characterized by deregulation of mature blood cell production and increased risk of myelofibrosis (MF) and leukemic transformation. Numerous driver mutations have been identified but substantial disease heterogeneity remains unexplained, implying the involvement of additional as yet unidentified factors. The inflammatory microenvironment has recently attracted attention as a crucial factor in MPN biology, in particular whether inflammatory cytokines and chemokines contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…In addition, like HGF and TNF-α, recent studies suggest that IL-1β favors MPN disease initiation and clonal expansion [ 54 , 63 , 64 , 65 ]. In the context of ET, Øbro et al reported that GRO-α and EGF (not measured in our study) were potential markers of disease progression, independently of JAK2 V617F or CALR mutation [ 66 ]. To summarize, the data indicate that IL-1β, IL-1Rα and IP-10 are linked to JAK2 V617F mutation, whereas all other cytokines in excess in MPNs are produced independently of JAK2 and CALR mutations but differentially according to the MPN phenotype.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, like HGF and TNF-α, recent studies suggest that IL-1β favors MPN disease initiation and clonal expansion [ 54 , 63 , 64 , 65 ]. In the context of ET, Øbro et al reported that GRO-α and EGF (not measured in our study) were potential markers of disease progression, independently of JAK2 V617F or CALR mutation [ 66 ]. To summarize, the data indicate that IL-1β, IL-1Rα and IP-10 are linked to JAK2 V617F mutation, whereas all other cytokines in excess in MPNs are produced independently of JAK2 and CALR mutations but differentially according to the MPN phenotype.…”
Section: Discussionmentioning
confidence: 85%
“…Of note, the main cellular source of GRO-α in ET has been identified in CD56+/CD14+ monocytes. Authors eventually introduced a novel prognostic model that incorporates cytokine profiling to well-established risk variables such as age, gender, and high-risk mutations [75]. As pointed out by Hasselbalch's commentary, this study highlights the prominent role of chronic inflammation in modulating MPN phenotype and course, and shows how the measurement of circulating cytokines may be an informative tool for patient risk stratification [76].…”
Section: Circulating and Bone Marrow Cytokine Levelsmentioning
confidence: 94%
“…Then, if we compare PMF with ET and PV (Table 2), surprisingly, not all inflammatory mediators are increased. Indeed, of the 29 cytokines whose levels and/or expression have been investigated in PMF as compared to the other two MPNs, 15 are increased (IL-2, sIL-2R, IL-6, IL-12, IL-17, TNF-α, INF-α, IL1RA, IL-4, IL-10, MIP-1β, RANTES, FGF, TPO, TGF-β) [63,70,72,80], IL1-α is similar [63], MCP-1 similar or increased, according to different studies [72,80], five cytokines are decreased (IL-7, VEGF, MIG, GRO-α, and CCL11) [70,75,79], and five show contradictory findings (both increased and decreased according to different reports: INF-γ, MIP-1α, IP-10, GM-CSF, EGF) [70,72,75,80]. The only mediators that are steadily elevated are pro-fibrotic cytokines, such as TGF-β, MCP-1, and FGF ( Table 2), suggesting that while inflammation is a common denominator of all three MPNs, PMF is characterized by a unique fibrogenic cytokine signature.…”
Section: Cytokine Gene Expression Profilingmentioning
confidence: 99%
“… 5 Our data reaffirms Øbro et al's observation that decreased levels of EGF is associated with progression to MF. 1 The expression levels for CCL11 (eotaxin) in platelets from all MPN subtypes were minimal and did not differ from controls. This is as expected, since eotaxin is mainly produced by structural and infiltrative inflammatory cells.…”
mentioning
confidence: 91%
“…We read with interest the recent publication by Øbro et al in HemaSphere documenting elevated cytokine levels in patients with myeloproliferative neoplasms (MPN). 1 Specifically, their finding of a signature associated with essential thrombocythemia (ET) that included three biomarkers: GRO-α, EGF and eotaxin. GRO-α was of greatest interest as elevated levels were associated with disease transformation to myelofibrosis (MF).…”
mentioning
confidence: 99%